SOSIALISASI TENTANG ASPEK HUKUM DALAM KEGIATAN BISNIS DI MARKETPLACE PADA SEKOLAH MENENGAH KEJURUAN NEGERI 9 BANDUNG - MUnaf, Carolina; Priowirjanto, Enni (PT. RANESS MEDIA RANCAGE, 2023)
Lack of understanding of legal aspects in businesS in the activities marketplace is one of the factors of ignorance of the rights and obligations of its users among high schools. This ignorance creates doubts and uncertainty about the importance of legal protection for them, especially when they are harmed by online businesses, because the products received are not in accordance with what was ordered. Departing from this thought, the Community Service Team of the Faculty of Law, Unvirsitas Padjadjaran, considered it necessary to conduct socialization to students and teachers from the State Vocational School 9 Bandung. Service activities begin with the delivery of material on legal aspects and business activities in the marketplace and examples of its application in one of the marketplaces in Indonesia. The results of the discussion on question and answer in the socialization carried out, it appeared that there was an increase in understanding from Teachers and Students of State Vocational High School 9 Bandung regarding legal aspects in business activities in the marketplace. The Community Service Team suggested that serious efforts should be made by teachers and students in trying to implement the knowlegde and understanding gained from the socialization.